Changes in the structure and composition of two Pinus nigra subsp. salzmannii forests over a century of different silvicultural treatments - Tiscar Oliver, P.A.; Lucas-Borja, M.E.; Candel Pérez, D. (Forest Systems, 2011)
Silvicultural treatments imply the felling of trees, which can modify species composition and structural diversity. Consequently, it is important to assess the influence of silvicultural treatments on forest composition and structure. The principal objective of this study was to analyze changes in the composition and structural diversity of two forests: Los Palancares y Agregados (Cuenca Mountain Range, Central-east of Spain) and Navahondona (Cazorla Mountain Range, Southeast of Spain), managed under two different silvicultural methods, i.e. shelterwood and selection. Forest inventory data, covering nearly a century of forest management, were used to follow changes in the number of trees and standing volume. Shannon’s index was computed for tree species composition and diameter classes, considering forest comparments as sampling units. Diversity profiles were constructed to follow changes in horizontal diameter class diversity. A partial redundancy analysis (pRDA) was conducted to asses the relative contribution of silvicultural treatments in explaining differences in the current structure of the two study forests. Results showed that silvicultural treatments favoured Spanish black pine and did not benefit other tree species. The number of large trees and the values of Shannon’s index decreased in both forests over the study period, but the forest under the uneven-aged silvicultural method showed higher values for both variables. Implications for sustainable forestry are discussed.